Heterogeneous nucleation of ice particles on glassy aerosols under cirrus conditions - Murray, Benjamin J.; Wilson, Theodore W.; Dobbie, Steven; Cui, Zhiqiang; Al-Jumur, Sardar M. R. K.; Möhler, Ottmar; Schnaiter, Martin; Wagner, Robert; Benz, Stefan; Niemand, Monika; Saathoff, Harald; Ebert, Volker; et al. (Nature geoscience, 2010)
Ice clouds in the tropical tropopause layer have a key role in dehydrating air that is entering the stratosphere. Cloud-chamber measurements suggest that their high humidity can be explained if heterogeneous ice nucleation on glassy aerosols is a significant nucleation mechanism in this region.
Gesehen am 17.05.2023